Specific features of the Czech language revival - Bláha, Ondřej (Bohemica Olomucensia, 2014)
The paper describes the main intentions of Czech linguists that resuscitate the standard Czech language at the beginning of the 19th century. The author shows how the derived words (at the expense of compound words) were preferred, just as borrowings from Polish and Russian - the symbolic functions of standard language were important factor here. It has the impact on the problems as well as strengths of the contemporary standard Czech language. It put a brake on the development of the Czech language in any case.